PHARMACOEPIDEMIOLOGIC ANALYSIS OF ST-ELEVATION MYOCARDIAL INFARCTION REPERFUSION THERAPY AT SARATOV REGION HOSPITALS OF DIFFERENT TYPES - O. V. Reshetko; N. V. Furman; R. M. Magdeev; Ya. P. Ya.P. Dovgalevskiy (Столичная издательская компания, 2016)
Aim. To evaluate the real practice of thrombolytic therapy of patients with ST-elevation myocardial infarction (STEMI) at cardiological departments of Saratov and Saratov region hospitals. Material and methods. Retrospective pharmacoepidemiologic study was carried out. Case histories of STEMI patients discharged from cardiologic departments of several central district hospitals (CDH) of Saratov region, cardiologic department of one of Saratov general municipal hospitals (MH) and urgent cardiology department of Saratov clinical hospital (CH) in 2006 were analyzed. Results. In CH all patients received thrombolytic therapy given they did not have contraindications and were admitted to the hospital timely. Few patients received thrombolytic therapy in MH and CDH in 2006. Conclusion. Correlation between hospital type and quality of STEMI management has been revealed.